Profile of vitamin D receptor polymorphism Bsm I and FokI in end stage renal disease Egyptian patients on maintenance hemodialysis - HA, EL-Attar; MM, Mokhtar; EW, Gaber (Journal of Clinical Nephrology, 2017)
Objective: In end stage renal disease, the synthesis of vitamin D is disturbed.Hyperparathyroidism is one of the key factors in the pathogenesis of many of the complications of dialysis mainly bone and cardiovascular complications.Aim:This study aimed at assessing vitamin D receptor gene polymorphisms BsmIand FokI in Egyptian patients with end stage renal disease on maintenance haemodialysis and the assosciation of these polymorphisms with cardiovascular complications and hyperparathyroidism among these patients. Methods: One hundred subjects, recruited from Medical Research Institute, from March to July 2014, divided into two main groups; the control group which included thirty apparently healthy subjects and the patients group which included seventy patients with end stage renal disease on maintenance haemodialysis with median 4 years. To all studied subjects, detailed history was taken, thorough physical examination, carotid intima media thickness, presence of plaques and ECG ischemic changes. Laboratory investigations included serum levels of: glucouse, urea, creatinine, uric acid, albumin, total cholesterol, low and high density lipoproteins, calcium, phosphorus, and CRP as well as plasma PTH level. For molecular studies, the detection of BsmI and FokI polymorphisms using polymerase chain reaction and restriction fragment length polymorphism (PCR / RFLP) technique. Results: 1.No statistically significant difference could be detected in both BsmI and FokI gene polymorphisms between the hemodialysis patients and the controls, suggesting that the development of ESRD had no relation with either VDR BsmI or FokI gene polymorphisms.2.No statistically significant difference were found in these polymorphisms between the hemodialysis patients with or without cardiovascular complications or between patients with PTH level less or more than 300 pg/ml. These results suggest that the development of cardiovascular complications and secondary hyperparathyroidism among Egyptian patients on maintenance haemodialysis cannot be attributed to these two gene polymorphisms. Conclusion: No association could be found between the variant alleles of BsmI and FokI gene polymorphisms and the development of ESRD, cardiovascular complications and secondary hyperparathyroidism among the studied samples of Egyptian patients on maintenance haemodialysis.